The performance of natural lighting in classrooms using shading devices - Maria Saraswati, Christi; Sahid, Sahid; Nogroho, Nancy Yusnita (ARTEKS : Jurnal Teknik Arsitektur, 2023)
One alternative energy source to replace fossil energy is sunlight. The presence of sunlight has an impact on the building in the form of heat radiation and natural lighting. Under certain circumstances, these two effects are contradictory. Buildings need natural lighting to reduce their reliance on artificial lighting, but adding this natural lighting also causes the building to become warmer, which will increase the energy required for air conditioning. One alternative solution to reduce the intensity of heat entering a building is the use of shading devices. The presence of sun shading is believed could be used to prevent heat radiation from entering the building, but the lighting intensity is not at its best. Educational buildings, particularly classrooms, are one type of building that utilizes natural lighting extensively. One of the educational buildings that has attempted to use shading devices. This research aims to determine the perfomance of natural lighting, especially uniformity in classsrooms that used shading devices. The research administers quantitative methods with Dialux Evo software simulation to determine the uniformity ratio of natural lighting in classrooms that use various forms of shading devices The research results reveal that the performance of classrooms with the four types of shading devices still does not meet standards. There is still a need for adjustments to the four types of shading devices so that their performance can meet standards